The IIUM: internationalizing higher education - Moten, Abdul Rashid (IIUM Press, 2009)
Introduction: The hallmark of the new millennium is the ever-increasing interdependence of people of various cultures. People, capital, ideologies, media images, and cultural impulses travel around the world more rapidly and efficiently than ever before. Responding to the needs of global man, higher education policies have become increasingly internationalized. Policy-makers and educators stress internationalization as a principal goal for higher education. This required them to bring about changes in the research agenda, alter the curricula, establish linkages with other centres of learning, and make the composition of professional staff and student bodies more pluralistic. The policies and practices undertaken by academic systems and institutions to cope with the global academic environment is generally referred to as internationalization.